2005
DOI: 10.1038/sj.emboj.7600761
|View full text |Cite
|
Sign up to set email alerts
|

The DASH complex and Klp5/Klp6 kinesin coordinate bipolar chromosome attachment in fission yeast

Abstract: We identified a truncated allele of dam1 as a multicopy suppressor of the sensitivity of cdc13-117 (cyclin B) and mal3-1 (EB-1) cells to thiabendazole, a microtubule poison. We find that Dam1 binds to the plus end of spindle microtubules and kinetochores as cells enter mitosis and this is dependent on other components of the fission yeast DASH complex, including Ask1, Duo1, Spc34 and Dad1. By contrast, Dad1 remains bound to kinetochores throughout the cell cycle and its association is dependent on the Mis6 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
147
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(164 citation statements)
references
References 50 publications
14
147
0
3
Order By: Relevance
“…By using strains that have a single Dam1 subunit tagged with GFP and expressed from the endogenous promoter (here, called mono-GFP-tagged Dam1), SpDam1 complex was previously detected to localize to kinetochores, the spindle, and intranuclear MTs in mitotic cells (20)(21)(22). In addition to these sites, by careful microscopic examination, we also detected weak, discrete spots of Dam1 assemblies on the interphase cytoplasmic MTs (Fig.…”
Section: Identification Of Discrete Dam1 Assemblies On Cytoplasmic Mtmentioning
confidence: 87%
See 1 more Smart Citation
“…By using strains that have a single Dam1 subunit tagged with GFP and expressed from the endogenous promoter (here, called mono-GFP-tagged Dam1), SpDam1 complex was previously detected to localize to kinetochores, the spindle, and intranuclear MTs in mitotic cells (20)(21)(22). In addition to these sites, by careful microscopic examination, we also detected weak, discrete spots of Dam1 assemblies on the interphase cytoplasmic MTs (Fig.…”
Section: Identification Of Discrete Dam1 Assemblies On Cytoplasmic Mtmentioning
confidence: 87%
“…20). Similar to ScDam1, SpDam1 is localized at kinetochores as well as on the spindle and the intranuclear MT (20)(21)(22), and functions in coupling kinetochores to MTs (22)(23)(24). Using quantitative fluorescence microscopy, it was determined that on average only seven to eight copies of SpDam1 per kinetochore were found (25).…”
mentioning
confidence: 99%
“…Ten S. pombe proteins, which are conserved in the S. cerevisiae DASH complex, were purified as a complex by biochemical purification . The DASH complex is localized at the kinetochore and the spindle at mitotic phase and functions with Klp5/6 to capture the kinetochore (Sanchez-Perez et al, 2005), indicating that it plays a role in spindle attachment during chromosome segregation. In addition to these mitotic centromere proteins, meiosis-specific centromere proteins, Sgo1 and Moa1, that play an important role in meiotic chromosome segregation have been characterized in S. pombe.…”
Section: Introductionmentioning
confidence: 99%
“…However, while such rings may efficiently couple microtubule depolymerization to chromosome movement in a system where kinetochores bind only to a single microtubule [130,131], they are not essential in fission yeast [132] and orthologues have never been found outside fungi. Additionally, it was subsequently shown that ring formation is not required for microtubule depolymerization-driven motion of the Dam1 complex [133,134].…”
Section: Force Generation By Microtubule Depolymerization From Plus-endsmentioning
confidence: 99%